Development of a novel nanocomposite consisting of 3-(4-methoxyphenyl)propionic acid and magnesium layered hydroxide for controlled-release formulation. Issue 10 (2nd July 2016) - Hashim, Norhayati; Misuan, Nor Saleha; Md Isa, Illyas; Kamari, Azlan; Mohamed, Azmi; Bakar, Suriani Abu; Hussein, Mohd Zobir
ABSTRACT: Magnesium layered hydroxide (MLH) intercalated with anionic 3-(4-methoxyphenyl)propionic acid (MPP) was synthesised by a direct reaction method using magnesium oxide and MPP as precursors. A further coating of chitosan was applied on the external surface of MLH–MPP nanocomposite to form a new material, named MLH–MPP/chitosan nanocomposite. The XRD pattern showed an intense and sharp peak at basal spacing 18.9 Å, proving that MPP anions were successfully intercalated into the interlayer gallery of MLH in a monolayer arrangement. The XRD pattern of the MLH–MPP/chitosan nanocomposite shows similar peaks with the MLH–MPP nanocomposite. The result was also supported by FTIR spectra and elemental analysis. TGA/DTG spectra showed that the thermal stabilities of the guest anion in the both nanocomposites were markedly enhanced. A controlled-release study of the MPP ion from the MLH–MPP/chitosan nanocomposite showed a slower release compared to MLH–MPP nanocomposite with an initial rapid release and slow release thereafter. Meanwhile, the release behaviours of MPP ions from both nanocomposites were governed by pseudo-second order kinetics. This result highlights the potential of the nanocomposite as an encapsulated material for the controlled-release formulation of MPP anions.